2008
DOI: 10.1007/s10681-008-9765-7
|View full text |Cite
|
Sign up to set email alerts
|

Seed parent breeding efficiency of three diverse cytoplasmic-nuclear male-sterility systems in pearl millet

Abstract: Pearl millet (Pennisetum glaucum (L.) R. Br.) hybrids, grown widely in India and to some extent in the US, are all based on an A 1 CMS source, leaving the pearl millet hybrids vulnerable to potential disease or insect pest epidemics. A comparison of this CMS system with two additional CMS systems (A 4 and A 5 ) in the present study based on isonuclear A-lines (seed parents) and their isonuclear hybrids showed that A-lines with the A 4 cytoplasm had much fewer pollen shedders and much reduced selfed seed set in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 14 publications
(14 reference statements)
0
16
0
Order By: Relevance
“…Of the three male-sterile lines used in this study, 5054A has been found to be most unstable for its male sterility as reflected in the relatively higher frequency of pollen shedders observed in this line (Rai et al 2008). It gave a 2-gene fit to 15F:1S ratio in the F 2 in both the seasons and to BC 1 ratio of 3F:1S in one season when crossed with L 67B, 3-gene fit to 54F:10S ratio in F 2 in both seasons, but lack of fit to the expected 3F:1S ratio in the BC 1 when crossed with IPC 511, lack of fit to any of these three hypothetical ratios in both populations and both seasons when crossed with IPC 804, and good fit to 3F:1S ratio in the summer season and to 54F:10S ratio in the rainy season in F 2 , but lack of fit to the expected ratios in both seasons in BC 1 when crossed with IPC 1518.…”
Section: Discussionmentioning
confidence: 93%
“…Of the three male-sterile lines used in this study, 5054A has been found to be most unstable for its male sterility as reflected in the relatively higher frequency of pollen shedders observed in this line (Rai et al 2008). It gave a 2-gene fit to 15F:1S ratio in the F 2 in both the seasons and to BC 1 ratio of 3F:1S in one season when crossed with L 67B, 3-gene fit to 54F:10S ratio in F 2 in both seasons, but lack of fit to the expected 3F:1S ratio in the BC 1 when crossed with IPC 511, lack of fit to any of these three hypothetical ratios in both populations and both seasons when crossed with IPC 804, and good fit to 3F:1S ratio in the summer season and to 54F:10S ratio in the rainy season in F 2 , but lack of fit to the expected ratios in both seasons in BC 1 when crossed with IPC 1518.…”
Section: Discussionmentioning
confidence: 93%
“…Also, an A 5 CMS system was identified in a pearl millet gene pool (Rai 1995). Among the various CMS systems reported so far, A 4 and A 5 CMS systems were found to have the most stable male sterility (Rai et al , 2001(Rai et al , 2006(Rai et al , 2009. Further, the frequency of maintainers is much higher for the A 4 CMS system than for the A 1 CMS system, and almost all lines are maintainers of the A 5 CMS system (Rai et al 2006).…”
mentioning
confidence: 99%
“…P earl millet is grown on 26 million ha in the semiarid tropics of Africa and the Indian subcontinent (Rai et al, 2009). It is a staple food for millions of poor people living in the dry areas of the world where it is difficult to grow any other crop.…”
Section: Researchmentioning
confidence: 99%